KARAKTERISTIK SPEKTRUM KEBISINGAN KENDARAAN SAAT BERHENTI - Dewi Muliana; Juandi '; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The Characteristics of Noise Spectrum for Vechicle at Rest condition at Jalan Soekarno Hatta, Pekanbaru, Indonesia. The research methodology uses Digital Voice Recorder experimentally and a GoldWave Software computes by a recorder. The measurement of noiseis detected at rest vehicle in four position having densed noise. First position has high peak and amplitude at Jalan Tuanku Tambusai 1. The other positions have low peak and amplitude at Jalan Soekarno Hatta 1, Jalan Tuanku Tambusai 2 and Jalan Soekarno Hatta 2 respectively. Noise signal is then evaluated at frequency 20 Hz - 20,000 Hz for all position. The intensityat position I has -85.0584 dB until -29.4942 dB, position II has -47.7043 dB until -84.5914dB , position III has -74.7860 dB until -46.7704 dB and position IVhas -74.7860 dB until - 46.3035 dB. The average noise spectrum intensity of vehicle against frequency y=Ax+B, where y is avarege spectrum intensity and x is frequency. The details is at position I (y=- 0.002x-35.93), at position II (y=-0.001x-52.01), at position III (y=-0.000x-54.81) and at position IV (y=-0.001x-50.24). In conclution, the spectrum of vehicle stop condition has low intensity.